ANTICIPATING THE SHALLOWING OF THE AQIDAH AND THE HERETICAL PRACTICE IN ACEH (Adnin International Multidiciplinary Journal, 2025)
Shallowing efforts of the faith (aqidah) of the Muslim community that occurred in Aceh prticularly post-tsunami until today are inevitable. That why it is need understood by all Acehnese Muslims for be careful in religious practice related with this challenge. This phenomenon is crusial enough since it is almost 100 percent of the population of the Aceh is muslim where the shallowing of the creed constitutes a sensitive issue in Indonesia, moreover in Aceh. The problem are whether the shallowinging of the religious faith takes place in Aceh and what the possible solution to cease this practice.This article aims at seeking an possible effort to solve the problem in harmony with existing laws and regulations for the praceful Acehnese people today, particularly as tbe mayority of Islamic community in this region. The data colection were conducted through library research with historical approach and the analysis of data using the qualitative technique. The result of research shows that since the tsunami volunteers who spread the mission of religions other than Islam might wrapped in the humanity assistance. When the Acehnese people were hit by very deep sorrow as the consequence of the earthquake and tsunami of 26 December 2004, Aceh was visited by various foreigners from various hemisphere of the earth for channeling humanity assistances, there was some good NGOs, national and international in character, that sliped to missionary activities afterwards.